Studi Fenomenologi Kebermaknaan Program Literasi bagi Guru dan Siswa di SMK Negeri 2 Sewon - Arifah Suryaningsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The low interest in reading has prompted the emergence of various innovative literacy programs in schools. However, many of these programs still rely primarily on quantitative measures of achievement, leaving their meaningfulness for teachers and students insufficiently understood. This study aims to uncover the meaning and essence of teachers’ and students’ experiences in implementing the “Jus Carica” literacy program at SMK Negeri 2 Sewon and to provide evidence-based recommendations for improving school literacy policies. A qualitative study with a transcendental phenomenology design (Moustakas, 1994) was employed, and data were collected through in-depth interviews, observations, and document analysis involving two teachers and three students with varying levels of reading interest. Data analysis was conducted through the stages of epoché, horizonalization, thematic clustering, the development of textural–structural descriptions, and synthesis of essence. The findings reveal that the program’s meaningfulness lies in the transformation of teachers’ roles from supervisors to facilitators, the enhancement of students’ self-confidence, greater personal relevance through autonomous theme selection, and flexible learning processes that foster creativity despite various constraints. The study concludes that the sustainability of the program depends on the provision of autonomy, humanistic facilitation, and methodological flexibility. Prospectively, similar models may be replicated in other vocational schools with appropriate contextual adaptation.